Hydrogen peroxide in breath condensate during a common cold - Rijn Q. Jöbsis; Susanne L. Schellekens; Anoeska Fakkel-Kroesbergen; Rolien H. C. Raatgeep; Johan C. de Jongste (Hindawi Limited, 2001)
Background: Hydrogen peroxide (H2O2) in exhaled air condensate is elevated in inflammatory disorders of the lower respiratory tract. It is unknown whether viral colds contribute to exhaled H2O2.